PENGARUH BINGO GAME TERHADAP KEMAMPUAN MEMBACA PERMULAAN ANAK USIA 4-5 TAHUN DI TK ISLAM FATIMAH KECAMATAN TAMPAN KOTA PEKANBARU - Wahyuni, Sri; Risma, Devi; Kurnia, Rita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This program is formal to know bingo games to read the binginning of the child 4-5 year in Tk Islam Fatimah sub district Tampan of Pekanbaru City. The research used experimental method with one group pre-test post-test design. The sampel used in this study were 20 students. The data collection technique used is observation. Technique of data analysis using t-test by using program of Spss 25. Research hypothesis that there is the effect of the role playing method towards the level of Self Awareness of children aged 4-5 years in Tk Islam Fatimah sub district Tampan of Pekanbaru City. Based on data analysis known tcalculated= 14,480 > ttable = 2,145 with Sig. (2-tailed) = 0.000. Because Sig <0,05. then it can be concluded that there are numbers the ability to read the binginning of a child before and after bingo game. it can be interpreted that there is the influence of bingo games on the child ability to read the binginning 4-5 year in Tk Islam Fatimah sub district Tampan of Pekanbaru City. which is significant which is equal to 61,25%Key Words: the ability to read the binginning of a child, bingo games